Deciphering the Roots of Pharmacists’ Critical Thinking About Pseudoscientific Claims: Insights from a Cross-Sectional Survey - Tomofumi Watanabe; Mari Matsumoto; Masami Ukawa; Makoto Ohira; Masaru Tsunoda (Pharmacy)
The global trend toward self-medication has increased public reliance on over-the-counter treatments and health-related information, contributing to the spread of pseudoscientific claims in healthcare and posing serious public health risks. Pharmacists, as accessible healthcare professionals, play a crucial role in critically evaluating these claims and providing evidence-based guidance. However, little quantitative research has assessed pharmacists’ critical thinking regarding pseudoscientific claims or the factors influencing them. This study aims to evaluate the demographic factors affecting pharmacists’ critical thinking about pseudoscientific claims. A cross-sectional survey was conducted among pharmacists in hospitals, insurance pharmacies, and drugstores across Japan. The newly developed Pseudoscience Criticism Scale (PCS) measured attitudes toward pseudoscientific claims. Statistical analysis identified factors that form and influence critical thinking. This study revealed two primary dimensions: “Medical Superstitions and Unscientific Treatments” and “Natural Healing Superstitions”. Gender and educational background significantly impacted PCS scores, with male pharmacists and graduates from six-year pharmacy programs exhibiting higher skepticism. These findings underscore the importance of ongoing professional development in pharmacy education to strengthen critical thinking. The PCS is an effective tool for assessing this competency. Enhancing educational efforts is essential to equip pharmacists to effectively counter pseudoscientific claims and improve public health.